2020
DOI: 10.1108/ajim-12-2019-0369
|View full text |Cite
|
Sign up to set email alerts
|

Can the adoption of health information on social media be predicted by information characteristics?

Abstract: PurposeThis paper aims to explore the relationship between the characteristics of social media health information and its adoption. The purpose is to identify information characteristics that can be used to estimate the level of health information adoption in advance.Design/methodology/approachAccording to the Information Adoption Model (IAM), the study extracted ten information characteristics from the aspects of information quality and information source credibility. The sample data was collected from the to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 59 publications
0
16
0
Order By: Relevance
“…Park (2020) demonstrated that three aspects of information value, namely, information credibility, information quality and information need are viewed as motivators of information adoption based on information acceptance model. Likewise, health information adoption was influenced by information features via social media (Sina Weibo), comprising information relevance and source credibility (Wang and Sun, 2020). Furthermore, Sixsmith (2020) stated that advanced technologies (e.g.…”
Section: Social Media-based Healthcare For Disease Information Exchangementioning
confidence: 99%
“…Park (2020) demonstrated that three aspects of information value, namely, information credibility, information quality and information need are viewed as motivators of information adoption based on information acceptance model. Likewise, health information adoption was influenced by information features via social media (Sina Weibo), comprising information relevance and source credibility (Wang and Sun, 2020). Furthermore, Sixsmith (2020) stated that advanced technologies (e.g.…”
Section: Social Media-based Healthcare For Disease Information Exchangementioning
confidence: 99%
“…argument quality) and extrinsic motivations (i.e. peripheral cues) (Wang and Sun, 2020). As one of the most commonly accepted theories in information system research, the ELM assists researchers in revealing the influence process itself.…”
Section: Theoretical Background and Research Model 21 Theoretical Bac...mentioning
confidence: 99%
“…According to previous studies, information characteristics influence credibility, attitude and information adoption in online review and social media (Park, 2020;Thomas et al, 2019;Wang and Sun, 2020), while others have demonstrated the formulation of health information acceptance in the general disease (Huo et al, 2018). The interpretation of a mechanism of health information acceptance via m-applications in the COVID-19 context is inadequate.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These routes are information quality as central route and source credibility as a peripheral route. In the current study, a detailed review was undertaken for information adoption model in various contexts including social media adoption (Chung, Han & Koo, 2015), eWom adoption (Filieri, Alguezaui, & McLeay 2015, Hussain et al, 2017, Purchase Intention (Khwaja, Mahmood & Zaman, 2020), online product adoption for new product development (Lee & Yang, 2014), travel websites adoption (Tseng & Wang, 2015), online reviews adoption (Shen, Zhang & Zhao, 2015), Health Sector (Wang & Sun, 2020).…”
Section: 1) Information Adoption Modelmentioning
confidence: 99%